The ThinkFeels Diary for exploring junior high school students' mental health in science class - Lilit Rusyati; Rika Rafikah Agustin; Ai Nurlaelasari Rusmana; Putri Sekar Melati; Nola Putri Erza; Andi Isni Pujirana; Siti Auliya Rahmah; Shopi Setiawati Maulidah; Kamilah Kurnia Nurlaeli; Achmad Ibrahim; Nisa Fauziah; Dyantie Nur Azizah; Azizah Qorina; Ade Setiawan; Isty Anggraeni; Salma Hayatun Nufuz (Journal of Environment and Sustainability Education, 2025)
This study investigated the effectiveness of ThinkFeels Diary as a meta-affective and meta-cognitive assessment tool in supporting students' mental health in science classrooms. The study used a mixed-method approach and included 205 students.  The ThinkFeels Diary, which allowed students to record both cognitive learning components and affective responses (emotions and feelings) during science courses, was the main component of the intervention. The MENTAL-Q questionnaire was used in pre-test and post-test designs to quantify the influence on mental health. Qualitative data from 3,840 student reflections were analyzed using NVivo 12. Results showed varied outcomes across classrooms. Two topics demonstrated significant changes: "The Nature of Science & Scientific Method" (p = 0.037, mean difference = -0.16) and "Measurement" (p = 0.018, mean difference = -1.41), both showing decreased mental health scores, possibly due to increased metacognitive demands. Analysis of sub-dimensions revealed complex patterns: the "Human Digestive System" topic showed notable improvements in empathy (+0.39) and adaptability (+0.37), though accompanied by increased depression (+0.38) and stress (+0.26).  According to the qualitative analysis, students’ emotional awareness (meta-affective) interacts dynamically with strategic thinking (meta-cognitive) before, during and after the learning. Reflection acts as a crucial link that turns experience into growth. This findings revealed the need of considering cognitive-emotional demands of different science topics to effectively support student mental health.